Life of Joseph Brant$1 (BThayendanegea (Vol. II) :s Including the Border Wars of the American Revolution and Sketches of the Indian Campaigns of Generals Harmar, St. Clair, and Wayne; And Other Matters Connected with the Indian Relations of the United States and Great Britain, from the Peace of 1783 to the Indian Peace of 1795 - Stone, William L. (William Leete), 1792-1844 (Salt Lake City, UT : Project Gutenberg, 2016)
"Life of Joseph Brant$1 (BThayendanegea (Vol. II)" by William L. Stone is a historical account written in the mid-19th century. The book chronicles the life of Joseph Brant, also known as Thayendanegea, focusing on his role during the border wars of the American Revolution and the related Indian campaigns. The narrative provides insights into the complex relationships between American settlers and various Native American tribes, as well as the strategic military actions taken during this tumultuous period. At the start of this volume, the narrative sets the stage for Sullivan's campaign against the Seneca tribes, highlighting the diverse characteristics among different Indian nations and the Americans' strategy of directly attacking their settlements. It discusses preparations for the campaign, including General Clinton's movements and the challenges faced in rallying Indian allies. The text emphasizes the misconceptions Europeans held about Native Americans, showcasing their distinct cultures and sophisticated societies, notably the Six Nations. It paints a vivid picture of the military landscape and the imminent clash between conflicting forces as Sullivan's troops get ready to embark on their mission of destruction and vengeance against the Indian settlements. (This is an automatically generated summary.)s
Release date is 2016-10-23
Produced by Roger Burch with scans from the Internet Archive.
Keywords: Indians of North America -- Wars -- 1750-1815; Brant, Joseph, 1742-1807; Mohawk Indians -- Kings and rulers -- Biography